Електронне урядування Естонії: досвід для України - Мина, Жанна; Гордійчук, Оксана; Яворська, Наталія (Видавництво Львівської політехніки, 2016)
This article describes that e-government is one of the essential factors in the development of the information society and a democratic society building. The current state of e-governance in Estonia is reviewed, the practical level of the country’s e-government is identified. The prospects of using e-governance in Ukraine are outlined.
Keywords: електронне урядування; державне управління; електронний уряд; взаємодія влади і громадян